3D modeling of indoor surfaces with occlusion and clutter - S. A., Abdul Shukor; K. W., Young; Rushforth, E. J. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/